1994
DOI: 10.1055/s-2007-1000793
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Modulates the Expression of Rat Liver Gammaglutamyl transpeptidase Activity

Abstract: Gammaglutamyltranspeptidase (GGT) activity is considered as a marker of liver phenotype, being maximally expressed in fetal liver and virtually absent in adult mature tissue. Since thyroid hormone has been identified to influence growth and development of almost all tissues, we have investigated the possible involvement of such factors in regulating rat hepatic GGT. Our results indicate that the activity of GGT in liver of perinatal hypothyroid rats is low as well as in control animals; instead, it is greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recently, a net increase in GGT activity in liver of methimazole-treated hypothyroid rats, which was completely prevented by T3-replacement therapy has been reported (Voci et at. 1994).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, a net increase in GGT activity in liver of methimazole-treated hypothyroid rats, which was completely prevented by T3-replacement therapy has been reported (Voci et at. 1994).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we have demonstrated that thyroid hormone, which influences growth and development of almost all mammalian tissues, regulates GGT expression in adult rat liver (Voci, de Marchis, Massajoli, Fugassa and Gallo 1994). It has been observed that the expression of GGT is increased in the liver of hypothyroid rat, whereas thyroid hormone replacement therapy decreases the enzyme expression suggesting a crucial role for thyroid function in maintaining the phenotype of adult rat liver.…”
Section: Introductionmentioning
confidence: 98%
“…In a recent study, Ruedig and Dringen (2004) reported that the cytokine TNFα elevates the specific activity of γGT in astrocyte cultures, an effect that is considered to be significant under pathological conditions. In cultures of hepatocytes (Voci et al, 1994; Demori et al, 1995), however, TH exerted a negative regulation of γGT. The molecular mechanism involved for the differential effect of the hormone on γGT: the positive effect of TH in astrocytes and the negative effect of the hormone in hepatocytes (Demori et al, 1995), is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step to elucidate the molecular basis of thyroidal regulation of GSH in the developing brain, we investigated thyroidal effects on γGT expression. Several earlier reports (Fernandez et al, 1991; Voci et al, 1994; Demori et al, 1995) describing the sensitivity of γGT to TH in liver were contradictory. Hemmings and Storey (1999) reported that congenital hypothyroidism had no effect on γGT in plasma membrane from neuronal or glial cells but reduced the activity of the enzyme by 33% in microvessels.…”
mentioning
confidence: 93%